(untitled) (Revista científica Olimpia, 2024)
This article is part of ongoing doctoral research. Its objective lies in exposing elements inherent to the professional improvement of the health rehabilitator for family guidance, based on the determination of detected insufficiencies, which impact the prevention of attention deficit/hyperactivity disorder. The deficiencies detected are corroborated from the initial verification applied to a sample of 12 health rehabilitators, belonging to the Tula Aguilera University Polyclinic, in the municipality of Camagüey. The theoretical methods used were analysis, synthesis, historical-logical, and induction-deduction. Observation and survey were used as empirical methods. The interview and questionnaire were used as techniques. Percentage analysis was used as a statistical-mathematical method. The results obtained confirm the insufficiencies in the professional improvement of the health rehabilitator for family guidance in the prevention of attention/hyperactivity disorder and the need to implement actions in this regard.